Prognostic Value of Ki 67 Proliferation Antigen in Canine Malignant Mammary Gland Tumours - Kadthur, Jayachandra C.; Rao, Suguna; Sonnahallipura, Byregowda M.; Thimmanahalli, Dayananda S.; Laxmikanth, Satyanarayana M. (Brazilian Journal of Veterinary Pathology, 2011)
Canine malignant mammary gland tumours were surgically resected from 78 dogs to determine the prognostic value of Ki 67 Proliferation antigen. After post surgical follow up for minimum of 1 year, 48 dogs were still alive, while 21 dogs had died as a consequence of malignancy, while remaining nine dogs showed recurrence of tumour. Formalin fixed, paraffin wax embedded histological sections were immunostained with monoclonal antibody Ki 67 (MIB -1). At least 100 cells in eight to 10 representative fields were counted. The Ki 67 index was expressed as the percentage of positive cells. In malignant canine mammary gland tumours, Ki 67 index ranged from 2.23 to 26.34 (14.45 ± 0.51). A statistically significant difference in the Ki 67 index (P< 0.05) was found between alive and dead group of dogs. Ki 67 index correlated with histological staging as most tumours in stage II had higher Ki 67 index and showed tumour related deaths. A clear association between the death due to malignancy and Ki 67 index was evident using Ki 67 index median count cut off value of 14.27 Thus Ki 67 index was good indicator of malignancy and dogs having Ki67 index greater than 14.27 have poor prognosis for mammary gland tumours.